Altered Gut Microbiota Contributes to Acute-Respiratory-Distress-Syndrome-Related Depression through Microglial Neuroinflammation - Bowen Zhu; Zheng Gu; Hongbin Hu; Jie Huang; Zhenhua Zeng; Haoxuan Liang; Ziyi Yuan; Shiwei Huang; Yuetan Qiu; Xiang-Dong Sun; Youtan Liu (Research)
Acute respiratory distress syndrome (ARDS) survivors often suffer from long-term psychiatric disorders such as depression, but the underlying mechanisms remain unclear. Here, we found marked alterations in the composition of gut microbiota in both ARDS patients and mouse models. We investigated the role of one of the dramatically changed bacteria—Akkermansia muciniphila (AKK), whose abundance was negatively correlated with depression phenotypes in both ARDS patients and ARDS mouse models. Specifically, while fecal transplantation from ARDS patients into naive mice led to depressive-like behaviors, microglial activation, and intestinal barrier destruction, colonization of AKK or oral administration of its metabolite—propionic acid—alleviated these deficits in ARDS mice. Mechanistically, AKK and propionic acid decreased microglial activation and neuronal inflammation through inhibiting the Toll-like receptor 4/nuclear factor κB signaling pathway. Together, these results reveal a microbiota-dependent mechanism for ARDS-related depression and provide insight for developing a novel preventative strategy for ARDS-related psychiatric symptoms.